Produção e caracterização de filmes de polpa de mamão com adições de nanoestruturas, processados em modo batelada - Barros, Taís Téo de (Universidade Federal de São Carlos, 2016)
The production of biodegradable films based on renewable low cost resources has increased considerably. The research and development of new materials in this segment make possible to replace, even still partially, the synthetic plastics derived from petrol and to add value to agro-industrial waste and agricultural commodities. The fruit purees (or pulp) represent an alternative for obtaining these low-cost arrays. It can be obtained from the fruit itself or from its processing wastes. Amongst the suited fruits for this purpose is the papaya (Carica papaya), largely available. Brazil is the largest producer of this fruit and, due to its high perishability, is a rich source of waste material for pulp and edible film processing. Although the films prepared from fruit puree lacks in mechanical and permeability properties, such features may be minimized by the addition of nanofillers associated to film forming biopolymers. Thus, the evaluation of papaya puree, in over-ripe stage, as raw material for film processing using a Mathis System (in batch mode) with reinforced nanostructure was the main aim of this study. The films were characterized considering mechanical and thermal properties, permeability, colorimetric and antimicrobial activity. The best results were recorded to formulations in which the pectin was added at 0.5 % (w/v), increasing the maximum fracture strength (σmax), in 12 times when compared to neat puree films (control). The insertion of cellulose nanofibers and chitosan nanoparticles also promoted a σmax increasing, nevertheless in inferior proportion (6.2 and 5 times respectively). The presence of pectin also was positive in reducing the permeability rates (WVP) with values of 77.72 % lower than those measured to the control films. Concerning the colorimetric properties, the films with filler additions (chitosan nanoparticles with glycerol) suffered the greater color changes (ΔE). The addition of chitosan nanoparticles also speed the surface browning index (BI). Again the pectin acted positively in preserving the original color characteristics. The antimicrobial essays indicated that the chitosan in nanoparticle format inside the polymeric matrix did not present any antimicrobial activity. The over-ripe papaya pulp showed to be a raw material suitable for edible biodegradable film processing and the addition of nanofillers and pectin necessary to improve the barrier and mechanical properties and to preserve the original colorimetric features.
Keywords: Filmes biodegradáveis; Filmes comestíveis; Nanopartículas de quitosana; Nanofibras de celulose; Processamento por batelada; Biodegradable films; Edible films; Chitosan nanoparticles; Pectin; Cellulosic nanofibers; Batch mode; Mathis; OUTROS